2020
DOI: 10.3390/jcm9030789
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Epidemic Peak of Coronavirus Disease in Japan, 2020

Abstract: The first case of coronavirus disease 2019 in Japan was reported on 15 January 2020 and the number of reported cases has increased day by day. The purpose of this study is to give a prediction of the epidemic peak for COVID-19 in Japan by using the real-time data from 15 January to 29 February 2020. Taking into account the uncertainty due to the incomplete identification of infective population, we apply the well-known SEIR compartmental model for the prediction. By using a least-square-based method with Pois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
301
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 283 publications
(321 citation statements)
references
References 14 publications
10
301
0
4
Order By: Relevance
“…Kuniya (2020) estimated the outbreak peak of coronavirus disease in Japan with the SEIR compartmental model [24]. In another study, the number of reproduction of the Wuhan novel coronavirus 2019-nCoV was estimated with the susceptible-exposed-infected-removed (SEIR) compartment model [25].There are studies on coronavirus disease by different researchers using various statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Kuniya (2020) estimated the outbreak peak of coronavirus disease in Japan with the SEIR compartmental model [24]. In another study, the number of reproduction of the Wuhan novel coronavirus 2019-nCoV was estimated with the susceptible-exposed-infected-removed (SEIR) compartment model [25].There are studies on coronavirus disease by different researchers using various statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate is lower than in SARS (Zhou, Yu et al 2020) but the incidence rate is significantly higher. The current COVID-19 epidemic differs in several aspects from the previous one caused by SARS, which was finally extinguished (Cossarizza, De Biasi et al 2020, Kucharski, Russell et al 2020, Kuniya 2020, Leung 2020, Mizumoto, Kagaya et al 2020, Parodi and Liu 2020. First, COVID-19 has a higher basic reproductive number, R 0 , than SARS.…”
Section: Introductionmentioning
confidence: 95%
“…The rapid increase in clinical cases of the new coronavirus disease, COVID-19, suggests that its transmissibility is high. Several studies indicated that the most probable basic reproductive number (R 0 ) is between two and four for the coronavirus (meaning that each infectious individual may directly generate two to four others) [1][2][3][4][5][6] . However, some estimates suggested R 0 higher than four with confidence intervals that reach values close to eight 2,7 .…”
Section: Introductionmentioning
confidence: 99%